A sutureless valve with sutures. Issue 7 (9th March 2022) - Moraes, Fernando; Mulinari, Leonardo
Abstract: The use of sutureless valves in infective endocarditis has been previously reported. Singh et al. have reported a single‐center successful surgical treated pulmonary endocarditis in two cases with a sutureless bioprosthesis.